Polimorfismos en el gen Amelx asociados a la susceptibilidad a caries en estudiantes unversitarios - de la Vega Calderón, Julieta (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
Among the factors that cause caries, are the microbiota of the oral cavity, dental anatomy, dental hygiene, dietary habits and susceptibility or resistance of the host. The studies about the genetic contribution to caries include genes involved in the immune response, genes involved in the saliva formation and composition, as well as those involved in enamel development; such as the AMELX gene, which encodes for the amelogenin protein. It has been reported in different countries, with the exception of Mexico, an association between a higher prevalence of caries and mutations in this gene. Objective: To detect the polymorphisms present in the AMELX gene and evaluate clinical factors which modulate caries in college students. Methods: We included 125 students, enrolled in UMSNH, to whom we determined the number of decayed pieces by the visual-tactile method, using a dental mirror and scanning probe. 10 mL of venous blood was collected from each patient for DNA extraction. DNA extraction was performed by the phenol-chloroform method. A fragment of AMELX gene was amplified by PCR assays, sequenced and compared to the sequences located in the GenBank data bases, using the BLAST algorithm tool. Pearson´s Chi square analysis was applied, to determine the association between caries and the factors that modulate it. Results: A 71.8% prevalence of caries was found. A relationship between the DMFT index and age was determined, finding a significance of 0.009; as well as a positive association between caries and the presence of rs5933871 and rs17878486 polymorphisms, with DMFT indices of 20 and 15 respectively, with a significance of 0.044. The DMFT index of zero was associated with absence of genetic polymorphisms on the studied gene. Conclusions: There is an association between the presence of caries and rs5933871 and rs17878486 polymorphisms in the AMELX gene of the studied population.

Entre los factores que causan la caries se encuentran la microbiota de la cavidad oral, la anatomía dental, los hábitos higiénico-dietéticos y la susceptibilidad o resistencia del huésped. Los estudios de la contribución genética a la caries incluyen genes asociados a la respuesta inmune, los involucrados en la formación y composición salival y los que participan en el desarrollo del esmalte, como el gen AMELX que codifica para la amelogenina. En distintos países se han reportado asociaciones entre una mayor prevalencia de caries y mutaciones en dicho gen, pero en México no se cuenta con estudios al respecto. Objetivo: Detectar los polimorfismos presentes en el gen AMELX y evaluar los factores clínicos que modulan la caries en estudiantes universitarios. Metodología: Se incluyeron 125 alumnos inscritos en la Universidad Michoacana de San Nicolás de Hidalgo a quienes se les determinó el número de piezas cariadas utilizando el método visual-táctil mediante espejo dental y sonda de exploración. De cada individuo se amplificó por PCR un fragmento del gen AMELX, y las secuencias obtenidas se compararon por el algoritmo Blast con secuencias depositadas en el GenBank. Para la asociación entre la caries y los factores que la modulan se aplicó el análisis de Chi cuadrada de Pearson. Resultados: Se determinó una prevalencia del 71.8% de caries. Se encontró una relación entre el índice CPO-D y la edad, con una significancia de 0.009; así como una asociación positiva entre la caries y la presencia de los polimorfismos rs5933871 y rs17878486, con índices CPO-D de 20 y 15 respectivamente, con una significancia de 0.044. El índice CPO-D de cero se relacionó con ausencia de polimorfismos genéticos. Conclusiones: Existe una asociación entre la presencia de caries y los polimorfismos rs5933871 y rs17878486 en el gen AMELX de la población estudiada.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-R-M-2015-1388; AMELX; PCR; ADN; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2967